Slavic-Albanian Language Contact: Lexicon - C. Curtis, Matthew (Slavia Centralis, 2020)
This paper examines the nature of Slavic and Albanian historical interactions on the basis of three approaches to lexical borrowings: Frans van Coetsem’s (1988/2000) concepts of borrowing and imposition, scales of borrowability as found in Thomason and Kaufman (1988), and Friedman and Joseph’s (2014) notion of ERIC loans (Essentially Rooted in Communication). By examining the geographic and semantic spread of vocabulary borrowed, Slavic appears to have had a greater influence in terms of geography and quantity of borrowings, while Albanian has also contributed words for kin and other categories likely borrowed under intense or prolonged contact, suggesting rich and diverse interactions that have occurred under a variety of circumstances, including times of peaceful coexistence.